Socioeconomic determinants of adolescent motherhood in Bangladesh (IIUC Business Review, 2026)
Bangladesh has a persistently high adolescent pregnancy rate, posing a public health risk. This study extracted 12680 women who had first birth at adolescent age from the Bangladesh Demographic and Health Survey 2017–18. Bivariate and multivariate logistic regression analyses were employed to identify the socioeconomic determinants of teenage motherhood. The study identified that women with a higher level of education (OR = 0.272), non-Muslims (OR: 0.523), who live in cities (in rural, OR: 1.095), who come from higher-income families (OR: 0.746), and who have a lower spousal age gap (spousal age gap more than 10 years, OR: 1.928) had less likely of having their first child at adolescent age. Policymakers need to emphasize economically empowering girls at the national and regional levels to reduce the rate of adolescent motherhood in Bangladesh.IIUC Business Review, Vol.-12, Issue-1, December 2023, pp. 61-74